The Headache in Emergency Departments study: Opioid prescribing in patients presenting with headache. A multicenter, cross‐sectional, observational study - Pellatt, Richard A. F.; Kamona, Sinan; Chu, Kevin; Sweeny, Amy; Kuan, Win Sen; Kinnear, Frances B.; Karamercan, Mehmet A.; Klim, Sharon; Wijeratne, Tissa; Graham, Colin A.; Body, Richard; Roberts, Tom; et al. (Headache, 2021)
Objective To describe the patterns of opioid use in patients presenting to the emergency department (ED) with nontraumatic headache by severity and geography. Background International guidelines recognize opioids are ineffective in treating primary headache disorders. Globally, many countries are experiencing an opioid crisis. The ED can be a point of initial exposure leading to tolerance for patients. More geographically diverse data are required to inform practice. Methods This was a planned, multicenter, cross‐sectional, observational substudy of the international Headache in Emergency Departments (HEAD) study. Participants were prospectively identified throughout March 2019 from 67 hospitals in Europe, Asia, Australia, and New Zealand. Adult patients with nontraumatic headache were included as identified by the local site investigator. Results Overall, 4536 patients were enrolled in the HEAD study. Opioids were administered in 1072/4536 (23.6%) patients in the ED, and 386/3792 (10.2%) of discharged patients. High opioid use occurred prehospital in Australia (190/1777, 10.7%) and New Zealand (55/593, 9.3%). Opioid use in the ED was highest in these countries (Australia: 586/1777, 33.0%; New Zealand: 221/593, 37.3%). Opioid prescription on discharge was highest in Singapore (125/442, 28.3%) and Hong Kong (12/49, 24.5%). Independent predictors of ED opioid administration included the following: severe headache (OR 4.2, 95% CI 3.1–5.5), pre‐ED opioid use (OR 1.42, 95% CI 1.11–1.82), and long‐term opioid use (OR 1.80, 95% CI 1.26–2.58). ED opioid administration independently predicted opioid prescription at discharge (OR 8.4, 95% CI 6.3–11.0). Conclusion Opioid prescription for nontraumatic headache in the ED and on discharge varies internationally. Severe headache, prehospital opioid use, and long‐term opioid use predicted ED opioid administration. ED opioid administration was a strong predictor of opioid prescription at discharge. These findings support education around policy and guidelines to ensure adherence to evidence‐based interventions for headache.